Strengthening effective government -citizen connections through greater civic engagement - Kirlin, John K.; Kirlin, Mary K. (2002)
Citizens are more frusting of government since the terrorist attacks ofr September 11, 2001, but their civic behaviors are little changed. One reason is that they mostly have been asked for monetary gifts to fund disaster relief and to serve others through existing nonprofit organizations. Available theoretical and empirical analyses suggest the three factors of motivation, skills, and network connections contribute to increased civic engagement, which is defined by behaviors such as seeking to persuade others to join in mobilizing commitment and resources to address a collective problem. Responses to 9/11 have not addressed these three factors. Increased civic engagement strengthens democracy and non cont ribute to the development of public judgment, which is critical to sustaining support of efforts to thwart terrorism. Success in any effort to increase civic engagement requires different strategies and actions by public officials. - Reproduced.
Keywords: State security - United States; State security